(untitled) (Nigerian Journal of Technology, 2022)
This work predicts rock fragmentation distribution and assesses the performance of the Kuz-Ram, Modified Kuz-Ram and Kuznetsov Cunningham Ouchterlony (KCO) models to determine the most accurate prediction model applicable for Aliko Resource Limited (ARL). The performance assessment was done using the Root Mean Square Error and Correlation and Regression Analysis. A general trend of prediction of more fines (<16.00 mm) and boulders (>800.00 mm) was observed for all the three models. The fragmentation results showed that there was a high quantity of fines with insignificant amounts of boulders produced from the blasts. Although all the models had a high correlation coefficient, R (> 95%), the Modified-Kuz-Ram model performed best for the blasts studied. It is therefore recommended for fragmentation prediction and blast optimisation studies of the mine.